Cadmium Exposure Inhibits Branching Morphogenesis and Causes Alterations Consistent With HIF-1α Inhibition in Human Primary Breast Organoids. (7th May 2018) - Rocco, Sabrina A; Koneva, Lada; Middleton, Lauren Y M; Thong, Tasha; Solanki, Sumeet; Karram, Sarah; Nambunmee, Kowit; Harris, Craig; Rozek, Laura S; Sartor, Maureen A; Shah, Yatrik M; Colacino, Justin A
Abstract: Developmental cadmium exposure in vivo disrupts mammary gland differentiation, while exposure of breast cell lines to cadmium causes invasion consistent with the epithelial-mesenchymal transition (EMT). The effects of cadmium on normal human breast stem cells have not been measured. Here, we quantified the effects of cadmium exposure on reduction mammoplasty patient-derived breast stem cell proliferation and differentiation. Using the mammosphere assay and organoid formation in 3D hydrogels, we tested 2 physiologically relevant doses of cadmium, 0.25 and 2.5 µM, and tested for molecular alterations using RNA-seq. We functionally validated our RNA-seq findings with a hypoxia-inducible factor (HIF)-1α activity reporter line and pharmaceutical inhibition of HIF-1α in organoid formation assays. 2.5 µM cadmium reduced primary mammosphere formation and branching structure organoid formation rates by 33% and 87%, respectively. Despite no changes in mammosphere formation, 0.25 µM cadmium inhibited branching organoid formation in hydrogels by 73%. RNA-seq revealed cadmium downregulated genes associated with extracellular matrix formation and EMT, while upregulating genes associated with metal response including metallothioneins and zinc transporters. In the RNA-seq data, cadmium downregulated HIF-1α target genes including LOXL2, ZEB1, and VIM . Cadmium significantly inhibited HIF-1α activity in a luciferase assay, and the HIF-1α inhibitor acriflavine ablated mammosphere and organoid formation. These findings show that cadmium, at doses relevant to human exposure, inhibited human mammary stem cell proliferation and differentiation, potentially through disruption of HIF-1α activity.